Aboriginal Policing in Rural Canada: Establishing a Research Agenda - Ruddell, Rick; Lithopoulos, Savvas (International Journal of Rural Criminology, 2013)
Canada’s First Nations Policing Program (FNPP) provides the funding and programmatic structure for policing 535 rural Aboriginal communities. After two decades and almost three billion (CA) dollars in expenditures, however, there has been comparatively little scholarly assessment of the strengths and weaknesses of this approach to policing. This study highlights the current state of the FNPP and we find that most government funded research has focused upon the administrative goals of the FNPP while relatively little government or scholarly attention has been paid to program outcomes. We identified three broad needs for Aboriginal policing research in Canada, including; (a) developing a research based inventory of best practices in rural and Aboriginal policing; (b) examining the efficacy of plural policing; and (c) how the study of Aboriginal policing can inform organizational theory. Each of these issues has implications for the development of research, practice, policy, and theory, and ultimately, ensuring just and fair outcomes concerning public safety for Canada’s Aboriginal peoples.